Microbial Community Field Surveys Reveal Abundant Pseudomonas Population in Sorghum Rhizosphere Composed of Many Closely Related Phylotypes - Chiniquy, Dawn; Barnes, Elle M.; Zhou, Jinglie; Hartman, Kyle; Li, Xiaohui; Sheflin, Amy; Pella, Allyn; Marsh, Ellen; Prenni, Jessica; Deutschbauer, Adam M.; Schachtman, Daniel P.; Tringe, Susannah G. (Frontiers in Microbiology, 2021)
While the root-associated microbiome is typically less diverse than the surrounding soil due to both plant selection and microbial competition for plant derived resources, it typically retains considerable complexity, harboring many hundreds of distinct bacterial species. Here, we report a time-dependent deviation from this trend in the rhizospheres of field grown sorghum. In this study, 16S rRNA amplicon sequencing was used to determine the impact of nitrogen fertilization on the development of the root-associated microbiomes of ten sorghum genotypes grown in eastern Nebraska. We observed that early rhizosphere samples exhibit a significant reduction in overall diversity due to a high abundance of the bacterial genus Pseudomonas that occurred independent of host genotype in both high and low nitrogen fields and was not observed in the surrounding soil or associated root endosphere samples. When clustered at 97% identity, nearly all the Pseudomonas reads in this dataset were assigned to a single operational taxonomic unit (OTU); however, exact sequence variant (ESV)-level resolution demonstrated that this population comprised a large number of distinct Pseudomonas lineages. Furthermore, single-molecule long-read sequencing enabled high-resolution taxonomic profiling revealing further heterogeneity in the Pseudomonas lineages that was further confirmed using shotgun metagenomic sequencing. Finally, field soil enriched with specific carbon compounds recapitulated the increase in Pseudomonas, suggesting a possible connection between the enrichment of these Pseudomonas species and a plant-driven exudate profile.